IMPROVING CORPORATE IMAGE BASED ON DIGITAL MARKETING AND SERVICE QUALITY IN CLINIC BUSINESSES - Rahmah, Fina Shofia; Maulana, Lucky Hikmat; Megawati, Dewi; Marlina , Asti (Fakultas Ekonomi Universitas Djuanda, 2025)
This study aims to analyze the image of Depi Alqorni Midwife Clinic based on digital marketing and service quality. The research method used is quantitative with data collection techniques through questionnaires that have been tested for validity and reliability distributed to 70 respondents who are users of Depi Alqorni Midwife Clinic. Data analysis methods used multiple linear regression, correlation coefficient analysis, coefficient of determination analysis, and statistical tests, using SPSS software version 23. The results of this study indicate that Digital Marketing and service quality simultaneously have a positive and significant effect on Company Image. Partially, it is known that Digital Marketing has no significant effect, while service quality has a positive and significant effect on the company image of Depi Alqorni Midwife Clinic. It is recommended to optimize social media, standardize service operational procedures, and focus on improving reputation and transparency in professional and ethical communication.